Designing Activities to Address Bullying Behavior Problems of Primary School Students in a Private School in Satun Province - Suksri, Jiraporn; Srisuk, Wanpichit (Journal of Thammawat, 2024)
This research is a qualitative study aims to analyze the problem conditions of bullying behavior and to design intervention activities to address bullying behavior among elementary school students at a private school in Satun province. In-depth interviews and group discussions are utilized in this study. The main informants include school administrators, student affairs teachers, subject teachers, students exhibiting bullying behavior, bullied students, parents, and clinical psychologists, totaling 31 individuals. The research findings indicate that: 1) The most common forms of bullying behavior among elementary school students were teasing about physical appearance, the belief in retaliation after being bullied, and ostracism from peer groups. 2) The intervention activities for addressing bullying behavior include (1) creating hypothetical scenarios depicting various types of violence to analyze and foster mutual understanding, (2) attitude adjustment activities to bolster self-confidence and self-awareness, (3) home room activities to facilitate teacher-student communication and awareness of student issues, and (4) extracurricular learning activities such as sports, singing, and music to promote camaraderie.